PERAN KNOWLEDGE SHARING SEBAGAI MEDIATOR PERCEIVED ORGANIZATIONAL POLITICS DENGAN INNOVATIVE WORK BEHAVIOR - Sri Raharso (Politeknik Negeri Bengkalis, 2020)
The purpose of the study was to examine the influence of perceived organizational politics on innovative work behavior and to identify the mediating effect of employees’ knowledge sharing. A questionnaire survey was carried out to 493 minimarket employees. Pearson’s correlation analysis was carried out to identify the characteristics of variables and their mutual relations, an multiple regression was also conducted for Baron & Kenny's (1986)’s mediated effect analysis. The finding suggests that there exists a negative relationship between perceived organizational politics and knowledge sharing, and a positive relationship between knowledge sharing and innovative work behavior. With regard to the role of knowledge sharing in the relation between perceived organizational politics and innovative work behavior, results of knowledge sharing as a full mediator have confirmed the hypothesis.